Desenvolvimento de um detector de espalhamento de luz LASER de baixo ângulo LALLS operando em tempo real na extrusão - Damiani, Juliano Conter (2005)
In the present work a prototype of a low angle laser light scattering was developed and installed in an extruder in order to operate in real time. The equipment was built by the research group of which the author is member, and low cost pieces were used when it was permitted. It was consisted of a laser beam which passes through the molten flow and a detector system formed by 64 photocells radially disposed to quantify the transmitted scattered beam. The molten flow used in this work was consisted of a PP matrix with a dispersed phase constituted of polymer (PA6, PS) or ceramic powder (TiO2, Al2O3). The resulting LALLS graphics showed dependence with second phase type. The signal from the detector is much stronger when ceramic powder was used. A dependence with the concentration was observed as well, as this factor affects the number of particles directly. The interpretation of the results was based on the considerations of Mie s theory, which correlates refraction indexes differences, particle size and concentration of the dispersed phase with the occurrence of single and multiple scattering. The measurements were all taken in the transient state, where the second phase is added in the polymer flow in the form of a pulse, and its behaviour is quantified in the extruder exit by the LALLS detector. Even when operating under severe conditions, like extrusion pressures (around 11 MPa) and temperatures (240°C or above), the detector showed enough sensibility to quantify the scattered light generated even by the blends used in this work.